2019
DOI: 10.1111/ijag.13565
|View full text |Cite
|
Sign up to set email alerts
|

Iron polyphosphate glasses for waste immobilization

Abstract: Iron polyphosphate glasses resist attack by water, can dissolve large concentrations of species that are otherwise insoluble in borosilicate glass melts, and can be processed at relatively low temperatures (1000‐1200°C), and so are viable hosts for vitrifying hazardous and radioactive wastes. The properties of iron polyphosphate glasses depend on the distributions of phosphate anions and the nature of the bonds between those anions and various metal polyhedra, and quantitative information can be obtained about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…6) Figure 4 shows the normalized mass release data of all cationic elements for the 15NaIP35, 15KIP35, 20CaIP35, and 20BaIP35 glasses. All NR i values are over two orders of magnitude lower than the United States Department of Energy (DOE) requirements for both high-and low-level activity wastes, 9,10) as shown in Table 1. All glasses released cations preferentially in the order R or RA > P º Fe, where R = Na, K and RA = Ca, Ba.…”
Section: Mcc-2 Static High-temperature Leach Test Methodsmentioning
confidence: 89%
“…6) Figure 4 shows the normalized mass release data of all cationic elements for the 15NaIP35, 15KIP35, 20CaIP35, and 20BaIP35 glasses. All NR i values are over two orders of magnitude lower than the United States Department of Energy (DOE) requirements for both high-and low-level activity wastes, 9,10) as shown in Table 1. All glasses released cations preferentially in the order R or RA > P º Fe, where R = Na, K and RA = Ca, Ba.…”
Section: Mcc-2 Static High-temperature Leach Test Methodsmentioning
confidence: 89%
“…Alternative host matrices, such as the iron phosphate glasses [Stefanovsky et al, 2017a] and lead iron phosphate glasses [Sales and Boatner, 1984], can offer a way of overcoming these shortcomings, since phosphate glasses have a much higher solubility for constituents such as halides, molybdenum, and zirconium. Research has suggested that iron phosphate waste forms can increase radioactivity concentrations (>2× greater) that can be safely stored and thereby decrease the total nuclear waste volume (>2× smaller) for storage and disposal [Brow et al, 2020]. However, phosphate glasses are known to react unfavorably with refractory materials [Tracy et al, 2021] including electrodes used in Joule-heated melters [National Research Council, Committee on Waste Forms Technology and Performance, 2011].…”
Section: Alternative Glass Systemsmentioning
confidence: 99%
“…Compared to borosilicate glass that is the most common nuclear waste vitrification matrix, iron phosphate glass (IPG) has lower melting temperatures and also higher waste loading capacity of sulfates, phosphates, chlorides, various heavy metals as well as chromium oxides 1,2 . However, its practical application is limited because the information on the loading of various nuclear waste components in IPG has not been studied extensively 3 . The 40Fe 2 O 3 –60P 2 O 5 stoichiometry of IPG has been optimized based on its chemical stability for nuclear waste loading.…”
Section: Introductionmentioning
confidence: 99%
“…The 40Fe 2 O 3 –60P 2 O 5 stoichiometry of IPG has been optimized based on its chemical stability for nuclear waste loading. It has a low melting temperature of ∼945°C and causes a lower extent of corrosion in the Inconel alloys and oxide refractory materials used in the vitrification process, which improves the lifetime of the melter 3–6 . The structure of IPG consists of a network of phosphate (mono‐, di‐, and tri‐forms) anions linked by tetrahedrally and octahedrally coordinated iron oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation